THE RELIGIOUS SITUATION TODAY IN KAZAKHSTAN - SMAGULOV, Kadyrzhan (CENTRAL ASIA AND THE CAUCASUS, 2011)
The events that occurred at the end of spring and the beginning of summer in 2011 in Kazakhstan (the suicide bomber in Aktobe, the attack on policemen by a group of extremists in the village of Shubarshi, and the threats from the Taliban to carry out terrorist acts in Kazakhstan if the country’s government decides to send Kazakhstan servicemen into Afghanistan) have riveted society’s attention on the religious situation that has developed in the republic today.It is worth noting in this respect that throughout the twenty years of the country’s independence, the top leaders of the Republic of Kazakhstan (RK) have never tired of repeating the need for stability in the interconfessional and ethnic spheres. However, state policy has failed to give the religious sphere its due attention, concentrating instead on enhancing economic development and reinforcing the position of the ruling regime. Leaving the religious sphere unattended has given missionaries from all over the world free license to come into the republic at will, whereby some of them are pursuing clearly extremist ends. Development of the situation along these lines has become possible for the following reasons.After the collapse of the Soviet Union, which failed, in the seventy years of its existence, to bring Communism as a guiding ideology to fruition, post-Soviet people, convinced of the utopianism of this idea, lost the moral reference point in their lives. The morals standards of decency, honesty, and discipline cultivated in the Soviet Union also fell into oblivion.The “barbaric” 1990s moved power, connections, so-called telephone justice (a particular stage of corruption whereby decisions were made and commands given over the phone rather than through legal mechanisms, thus creating virulent lawlessness), pulling strings, and other defects characteristic of a degenerating society to the forefront. So, having lost their former ideals, people began looking for new foundation stones to build their world outlook on. This led to the ensuing vacuum being filled with all manner of new ideas largely promoted by the liberal legislation. The difficult time of building an independent state produced a large number of ethically challenged and unconscientious citizens who are trying to commercialize public conscience.During its first years of independence, the state essentially paid no attention to the religious sphere, since it was too busy resolving economic issues and building the political regime, although the latest events in the RK have proven the erroneousness of this strategy.